Surface deformation field and fracture propagation mechanism of rock-like specimen with pre-existing fracture - Zhaohui WANG; Wenchao SUN; Xuebing WANG; Bokai QIAO (Meitan kexue jishu, 2023)
Eastern coalfield goes into deep mining gradually in China. Fracture development rises greatly in surrounding rocks, increasing the difficulty in ground control under increased mining disturbance. In order to reveal failure mechanism of fractured rocks and improve ground control of deep coal mine, the influence of fracture angle on mechanical behavior, surface strain field and fracture propagation is analyzed by using uniaxial compression test combined with DIC technique. The results show that stress-strain curve of rock specimen with pre-existing fracture presents double-peak shape, induced by shear inter-locking effect between pre-existing and newly-developed fractures. With the growth in fracture angle, elastic modulus and damage degree rise in rock specimen while uniaxial compressive strength (UCS) experiences decreasing and subsequent increasing stages, respectively. Quantitative relationship between the UCS and fracture angle is deduced. Preponderant dip angle is defined for failure of rock with pre-existing fractures and the value is 45° when the fracture belongs to open-type. Deformation localization rock with pre-existing fractures occurs at the fracture tip. The initiation stress reaches 80% of initial yield stress when localization area is dominated by tensile stress, and the percentage decreases to 60% when dominated by shear stress. Propagation path of deformation localization area is consistent with that of surface fracture. Rock deformation stage transits from strain localization to fracture development when strain magnitude reaches 5.0%. Rock specimen fails in tension and shear mixed mode when fracture angle is 60° or 75°. Otherwise, only tension failure is observed in the loading process. It takes longer to form a tensile fracture and horizontal displacement curves of feature points on two sides deviate from each other. It takes shorter to form a shear fracture and vertical displacement curves show deviation trend. Grain based model (GBM) is developed for fractured specimen, which indicates small crack development is dominated by tensile type. Shear crack experiences both rising and subsequent declining stages with the growth in fracture angle. With the DIC technique, failure position, failure time and fracture propagation path can be predicted, which provides valuable precursor for instability prevention of surrounding rock at depth.